2023
DOI: 10.1002/1878-0261.13431
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐mediated regulation of DDX5 through decreased chromatin accessibility and post‐translational targeting restricts R‐loop accumulation

Abstract: Local hypoxia occurs in most solid tumors and is associated with aggressive disease and therapy resistance. Widespread changes in gene expression play a critical role in the biological response to hypoxia. However, most research has focused on hypoxia-inducible genes as opposed to those that are decreased in hypoxia. We demonstrate that chromatin accessibility is decreased in hypoxia, predominantly at gene promoters and specific pathways are impacted including DNA repair, splicing, and the R-loop interactome. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…2 H). Consistently, decreased DDX5 expression is associated with R-loops accumulation in cancer cells [ 40 ]. This finding suggests that DDX5 also plays a critical role in hypoxia response by increasing R-loop-associated DNA damage resulting from hypoxia-mediated inhibition of DDX5.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…2 H). Consistently, decreased DDX5 expression is associated with R-loops accumulation in cancer cells [ 40 ]. This finding suggests that DDX5 also plays a critical role in hypoxia response by increasing R-loop-associated DNA damage resulting from hypoxia-mediated inhibition of DDX5.…”
Section: Introductionmentioning
confidence: 83%
“…Additionally, Leszczynska et al found that hypoxia decreases DDX5 expression and chromatin accessibility at gene promoters and impacts specific pathways [ 40 ]. This may include mRNA stability, DNA topological regulation, DNA repair, RNA splicing, and ribosome biogenesis (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that DDX5 expression levels were reduced under hypoxic conditions in various cancer cell lines, including RKO and HCT116, and so on (Leszczynska et al., 2023). However, under our experimental setup and hypoxic conditions, we observed no apparent change in the expression levels of DDX5.…”
Section: Discussionmentioning
confidence: 99%
“…Several helicases belonging to the DEAD/H-box family have been reported to prevent R-loop accumulation. DDX5 has been reported to resolve R-loops by different groups ( 37 , 76 , 77 , 78 , 79 ). DDX18 can inhibit the accumulation of R-loops mediated by PARP-1 (poly[ADP-ribose] polymerase-1).…”
Section: R-loop Resolution Helicasesmentioning
confidence: 99%